2021
DOI: 10.1080/15476286.2021.1882180
|View full text |Cite
|
Sign up to set email alerts
|

Identification of RNAs bound by Hfq reveals widespread RNA partners and a sporulation regulator in the human pathogen Clostridioides difficile

Abstract: Noncoding RNAs (ncRNA) have emerged as important components of regulatory networks governing bacterial physiology and virulence. Previous deep-sequencing analysis identified a large diversity of ncRNAs in the human enteropathogen Clostridioides (Clostridium) difficile . Some of them are trans -encoded RNAs that could require the RNA chaperone protein Hfq for their action. Recent analysis suggested a pleiotropic role of Hfq in C. difficile wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 117 publications
3
29
0
Order By: Relevance
“…In addition, all but one type-I antitoxin transcript were enriched (Fig. 5A and Dataset S6), similar to a recent RIP-seq analysis of Hfq in C. difficile (20). Classifying Hfq-associated sRNAs with respect to their genomic location revealed that the majority of cis-antisense-encoded sRNAs in C. difficile were bound by Hfq, as well as approximately one-half of all intergenic, 5′ UTR-, and 3′ UTR-encoded sRNAs (Fig.…”
Section: Microbiologysupporting
confidence: 86%
See 3 more Smart Citations
“…In addition, all but one type-I antitoxin transcript were enriched (Fig. 5A and Dataset S6), similar to a recent RIP-seq analysis of Hfq in C. difficile (20). Classifying Hfq-associated sRNAs with respect to their genomic location revealed that the majority of cis-antisense-encoded sRNAs in C. difficile were bound by Hfq, as well as approximately one-half of all intergenic, 5′ UTR-, and 3′ UTR-encoded sRNAs (Fig.…”
Section: Microbiologysupporting
confidence: 86%
“…Hfq bound mostly to the 5′ and 3′ UTRs of target mRNAs, and of note, many enriched 5′ UTRs harbored a riboswitch or PTT (66/124 5′ UTRs) (Fig. 5A) as recently observed in an independent Hfq RIP-seq analysis (20). Many mRNAs showed growth phase-dependent association with Hfq (SI Appendix, Fig.…”
Section: Microbiologysupporting
confidence: 67%
See 2 more Smart Citations
“…In S. aureus , the expression and role of Hfq appear to be strain specific, and the deletion does not seem to have the highly pleiotropic effects seen in E. coli hfq mutants ( 25 , 26 ). The exception to the rule may be Clostridioides difficile where deletion of hfq affects expression of 224 genes (5% of genes, compared with 785 [18%] of genes in Salmonella Typhimurium [ 27 ]) and has pleiotropic effects on sporulation, growth, morphology, and stress responses ( 28 ). Hfq binds and stabilizes a subset of sRNAs in C. difficile ( 28 , 29 ), and, importantly for the discussion below, recent Hfq RNA immunoprecipitation sequencing (RIP-seq) experiments have identified 18 3′ UTR-encoded sRNAs, including five type II 3′ UTR sRNAs ( 29 ).…”
Section: Rna Metabolism Has Diverged Between Model Proteobacteria and Firmicutesmentioning
confidence: 99%